RISK MANAGEMENT ANALYSIS AT PT IRA JAYA SATRIA USING THE RISK REGISTER METHOD - Syahputri, Kharisma; Sugianto; Rahma, Tri Inda Fadhila (Pena Cendekia Insani, 2025)
In an increasingly dynamic business environment, companies face various risks that can affect operational stability and business sustainability. This study aims to analyze the implementation of risk management at PT Ira Jaya Satria using the risk register method. This method allows the company to systematically identify, analyze, and manage risks. The research employs a qualitative approach with data collection techniques through interviews and documentation.The findings indicate that PT Ira Jaya Satria faces several key risks identified in this study, including operational risks related to machinery breakdowns, safety risks associated with workplace accidents, and financial risks due to delayed payments from clients. The analysis shows that the risks encountered fall within a moderate category, with a percentage of 40%-60%. Through the application of the Risk Register, the company can enhance the effectiveness of risk management, reduce negative impacts, and improve operational efficiency. Well-integrated risk management not only protects the company from potential losses but also contributes to the achievement of strategic objectives and business sustainability in the future.